Optimization of the gas flow system in a selective laser melting chamber using numerical methods - Zhou, Zirong; Li, Yongxing; Chen, Xiaoxuan; Shang, Xin; Gou, Kunzheng; Pang, Lijuan (Advances in mechanical engineering, 2024)
A well-designed flow field is a key factor to improve the surface quality of products by removing spatter, which is often generated during the selective laser melting (SLM) process. In the present study, three typical schemes are developed for the gas flow system of large-scale SLM equipment. In this regard, the flow deviation and velocity increase indices are implemented to characterize the flow uniformity in the chamber and gas flow velocity in the clearing area. The obtained results show that the inlet size significantly improves the flow uniformity and the segmented inlet increases the flow velocity above the machining surface. More specifically, when the velocity deviation index decreases from 0.3335 to 0.1538, the corresponding velocity index increases from 10.16% to 29.83%. To improve the flow uniformity on the machining surface, the effect of the inlet flow rate on the airflow over the machining surface is investigated. The obtained results show that when the inlet flow rate reduces to 0.2 m/s, the removal spatter improves while the airflow remains uniform. The results of this study can provide a reference for the design of SLM gas flow systems.